A Cyberphysical System Based Mass-Customization Approach with Integration of Industry 4.0 and Smart City - Karakose, Mehmet; Yetis, Hasan (Wiley-Hindawi, 2017)
Smart city is a city which is designed to meet the people's demands. In addition to use of sources efficiently, trends of people are also a need that smart city shouldmeet. Buying personalized products in a cheap and fast way is a demand of people of today. Mass customization, which is defined as the personalization of products, achievesmaking the tailor-made products cheaper. In this study, we propose a new approach for mass customization with the integration of smart retail and smart production. With removing the operators and actualizing the progress autonomously, it is aimed to reduce the waiting time of customers. Because less waiting time means that there are more mass-customization customers, and this is expected to increase the popularity of mass customization. Thus, reducing wastes and increasing productivity are aimed. This study also constitutes the infrastructure that enables a production system to autonomously perform all stages from order to delivery. With the given scenarios, challenges and advantages of desired approach are discussed.